Adalimumab treatment in Japanese patients with generalized pustular psoriasis: Results of an open‐label phase 3 study. Issue 12 (10th October 2018) - Morita, Akimichi; Yamazaki, Fumikazu; Matsuyama, Takashi; Takahashi, Kenzo; Arai, Satoru; Asahina, Akihiko; Imafuku, Shinichi; Nakagawa, Hidemi; Hasegawa, Yuichi; Williams, David; Matsuda, Naoto; Kitamura, Susumu
Abstract: A phase 3, multicenter, open‐label, 52‐week study investigated the efficacy and safety of adalimumab 80 mg at week 0 followed by adalimumab 40 mg every other week (option to escalate to 80 mg when necessary) in Japanese patients with generalized pustular psoriasis (GPP). Adults (aged 15–75 years) with GPP, total skin score (overall erythema area, erythema area with pustules, and edema area) of 3 or more, and erythema with pustules (skin score, ≥1) based on the 2014 Japanese Dermatological Association severity index of GPP were enrolled. The primary efficacy end‐point was clinical response at week 16 (non‐responder imputation), defined as achieving remission (total skin score, 0) or improvement from baseline (reduction of ≥1 point from a baseline total skin score of 3 or ≥2 points from a baseline total skin score of ≥4). Of 10 enrolled patients (mean disease duration, 10.6 years), seven patients, including three with the dose escalated to 80 mg every other week before week 15, achieved clinical response at week 16, and five achieved clinical response at week 52. Mean change from baseline total GPP score was −4.6 at week 16 ( n  = 8) and −6.0 at week 52 ( n  = 5); change in total skin score was −3.1 ( n  = 8) and −4.2 ( n  = 5), respectively. Nine patients experienced one or more adverse events and three experienced serious adverse events. The most common adverse events were nasopharyngitis, pruritus and hypoalbuminemia. In conclusion, adalimumab was effective and well tolerated for up to 52 weeks in the treatment of Japanese patients with GPP.